DOES INVESTORS RESPOND TO TAX AVOIDANCE AND TAX RISK? STEWARDSHIP PERSPECTIVE - Amrie Firmansyah; Taufik Tri Widodo (Bina Ekonomi, 2021)
This study investigates the association of tax avoidance and tax risk with investor responses regarding firm value in Indonesia. The methodology of this study is the quantitative method. The secondary data were sourced from companies' financial statements and stock prices in the consumer goods industry sector listed on the Indonesia Stock Exchange from 2017 to 2019, obtained from www.idx.co.id, www.idnfinancials.com, and www.finance.yahoo.com. Based on purposive sampling, the number of samples in this study amounted to 78 observations. Hypothesis testing employed in this study is multiple regression analysis for panel data. This study suggests that tax avoidance is positively associated with firm value, but tax risk is negatively associated with firm value. Tax avoidance is an activity that can align the interests of shareholders. Meanwhile, tax risk tends to occur beyond the control of managers so that managers cannot take advantage of tax risk to support the interests of shareholders. This study indicates that the Financial Services Authority needs to coordinate with the Indonesian Tax Authority in improving regulations related to tax avoidance by issuers in Indonesia.